MINAT BELI MASYARAKAT DITINJAU DARI PENGARUH IKLAN TV, CITRA MEREK, DAN DESAIN PRODUK PADA SARUNG CAP GAJAH DUDUK (Studi Empiris Pada Masyarakat Muslim Desa Koripan Kecamatan Matesih Kabupaten Karanganyar) - Alfi Annur Rohman; Sri Wijiastuti; Abdullah Zailani (Universitas Bina Taruna Gorontalo, 2023)
The aims of this study were 1) to test and analyze the partial effect of TV commercials, brand image and product design on buying interest in Gajah Dut stamp sarongs. 2) To find out the factors that have the most dominant influence on the interest in buying Gajah Dut stamp sarongs. 3) To test and analyze the influence of TV Ads, Brand Image, and Product Design simultaneously on the intention to buy the Gajah Dut stamp sarong. In this study, researchers used quantitative research with data collection methods through questionnaires and library document data. With a population of all Muslim communities in the Koripan Village, Matesih District. By taking a sample of 100 respondents through the accidential sampling method. By conducting data analysis through research instrument tests, classical assumption tests, linear regression tests, hypothesis testing. The results of the study found that both partially and simultaneously there was a positive and significant influence on television advertising, brand image and product design on the intention to buy the Gajah Dut stamp sarong. The brand image variable in this study is the variable that has the most dominant influence on the intention to buy the Gajah Gajah sarong. Purchase intention can be explained by television commercials, brand image and product design by 56.20%. While the remaining 43.80% is explained by other factors outside of this study.